Malaysia's plantation industry and economic crisis: Issues on crisis management - Alias, Mohammad; Maamor, Selamah; Berawi, Mohd Fuad (2001)
The Malaysian plantation industry is an integral part of the agricultural sector.The major crops produced are palm oil, rubber and cocoa.While in the past a large proportion of the crops produced were exported as raw materials, an increasing proportion of domestic production of these commodities is now processed locally into manufactured products.It is well known fact that the markets for primary commodities are characterized by instability, in prices due to inelastic supply and demand.Business cycles in major importing countries, developments in competing products markets (soyabean in the case of palm oil, and synthetic rubber in the case of natural rubber) and exogenous events such as wars and major and protracted climatic changes, would impact on the palm oil, rubber and cocoa markets. The main objective of this paper is to discuss on issues of crisis management of the plantation industry.We want to focus on the impact and resolution of crisis brought about by business cycles, especially in major importing countries.We review the impact of past economic crisis, in particular the 1985 and 1998 economic recessions on the Malaysian plantation industry.In each case, we will look at the causes of the recessions, response of the Government and the producers, and suggest what lessons have been learnt in terms of crisis anticipation and resolutions.The study also examines the likely impact of the US economy's slowdown on the economy in general, and the plantation industry in particular.